Pediatric Tape - Jaksic - Horvat, Kornelija (Journal Resuscitatio Balcanica, 2021)
Introduction: Care and management of a life threatened child is a stressful event per se, further aggravated by the need for precise calculation of medication doses, the amount of fluids for volume replacement and choosing the rightsized equipment based on child’s weight and age, which is often an information unavailable at the scene of the emergency event. Objective: Our objective was to make a pediatric tape modeled by Broselow tape, but modified for medications and overall conditions present in our region. The original Broselow tape is not available in our country. Method and materials: For tailoring this pediatric tape we used the original Broselow tape.The connection between length/height of a child and its body weight was used in the same way, and then doses of medications and sizes of medical equipment were calculated for the appropriate age/body weight. Discussion: Our pediatric tape has two measuring parts: measuring tape with colored zones and cards that follow the appropriate color. Tape is divided into nine zones with calculated doses of medications, the amounts of fluids for volume replacement and sizes of equipment for each zone. Conclusion: Hoping that this pediatric tape will find its place and use in our region, we hereby open a discussion of our professional community regarding this accessory and its future potential.